Materialidad de la devoción medieval en el Libro de los tres reyes de Oriente - Zubillaga, Carina (El Colegio de México, 2023)
Since a medieval codex is, among other things, a cultural, material object, this paper argues that the handwriting in the document ─given the primacy of vision over the other bodily senses─ has a predominantly visual significance. Based on this premise, the paper offers a study of the visual and textual aspects of manuscript K-III-4 of the Libro de los tres reyes de Oriente, and presents it as an excellent example of the material aspects of medieval devotion and of its concrete and symbolic relevance.